Dampak Implementasi Flexible Working Space (FWS) terhadap Kinerja Sumber Daya Manusia pada Instansi Kementerian Keuangan - Sani, Andrew Setiawan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The world of work has undergone a significant transformation in recent years, driven by technological advancements and changing employee mindsets. Flexible Working Space (FWS) has emerged as a new work concept that offers flexibility in time and work location for employees. This concept has attracted the attention of many organizations because of its potential to improve employee productivity, performance, and job satisfaction. The author's purpose in this study is to find out the extent to which the impact of flexible working space (FWS) encourages a new cultural change in the implementation of the work system within the Ministry of Finance Organization, namely flexibility in the arrangement of work locations, which includes the implementation of official duties in the office (WFO) and/or the implementation of official duties by implementing a flexible working space (FWS) flexibility mechanism. This study uses qualitative methods to collect data from various sources, including surveys and interviews.